2019
DOI: 10.1111/liv.14187
|View full text |Cite
|
Sign up to set email alerts
|

Stereotactic image‐guided microwave ablation of hepatocellular carcinoma using a computer‐assisted navigation system

Abstract: Background & Aims:Ablation plays an important role in the treatment of hepatocellular carcinoma. Because image-guided navigation technology has recently entered the clinical setting, we aimed to analyse its safety, therapeutic and procedural efficiency. Methods: Retrospective analysis of patients treated with stereotactic image-guided microwave ablation (SMWA) between January 2015 and December 2017. Interventions were performed using computertomography-guidance with needle trajectory, ablation planning and aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 45 publications
(47 reference statements)
1
47
0
Order By: Relevance
“…While little is known about factors influencing targeting accuracy and therapeutic efficacy when using such navigation systems for stereotactic tumor targeting, they likely facilitate accessibility and treatment of traditionally difficult to target liver tumors (28). Our group has previously reported the benefits of using stereotactic imageguided microwave ablation (SMWA) in the treatment of HCC (29). The aim of the current study was to investigate factors influencing targeting accuracy and treatment efficacy when using SMWA for malignant liver tumors in a multivariable model that includes challenging lesion locations.…”
Section: Introductionmentioning
confidence: 99%
“…While little is known about factors influencing targeting accuracy and therapeutic efficacy when using such navigation systems for stereotactic tumor targeting, they likely facilitate accessibility and treatment of traditionally difficult to target liver tumors (28). Our group has previously reported the benefits of using stereotactic imageguided microwave ablation (SMWA) in the treatment of HCC (29). The aim of the current study was to investigate factors influencing targeting accuracy and treatment efficacy when using SMWA for malignant liver tumors in a multivariable model that includes challenging lesion locations.…”
Section: Introductionmentioning
confidence: 99%
“…All of the 34 included works were single-centre studies, of which 26 were retrospective studies (29,30,(39)(40)(41)(42)(43)(44)(45)(46)(47)(48)31,(49)(50)(51)(52)(53)(54)(32)(33)(34)(35)(36)(37)(38), 3 prospective case series(55-57), 3 prospective cohort studies(58-60) and 2 randomised controlled trials (61,62). Two studies reported results using a laparoscopic treatment access (44,55), the other 32 reporting on thermal ablations using a percutaneous approach.…”
Section: Resultsmentioning
confidence: 99%
“…There are also large retrospective studies showing the potential benefits and applications of stereotactic image-guided ablations. While these studies do not show better oncological outcomes when using stereotactic ablation over conventional ablation, they state that the number of patients treated with a curative intent largely increased with the introduction of stereotactic guidance [1,30,31]. Furthermore, it has been shown in case-reports that stereotaxy was especially useful in very difficult cases when the tumor would not be reachable with conventional CT guidance [32].…”
Section: Current Evidence and Future Perspectivesmentioning
confidence: 99%